Chemometric-empowered spectroscopic techniques in pharmaceutical fields: A bibliometric analysis and updated review - Zulkifli, Baidillah; Fakri, Fajar; Odigie, Joan; Nnabuife, Loveday; Isitua, Chinwe C.; Chiari, Williams (Narra Sains Indonesia, 2023)
Undeniable increase in pharmaceutical demand has encouraged researchers to develop analytical techniques to analyze drugs and monitor their effects. Chemometrics enabled simple spectroscopic approaches (such as infrared or UV spectroscopy) to analyze complex samples, including drug formulations, excreted fluids and tissues of living organisms. The aim of this study was to evaluate the research trend of this combinatorial technique utilized for pharmaceutical-related sample analysis using a bibliometric analysis. Bibliometric data of published literature from the Scopus database on March 14, 2023 were retrieved using the keyword combinations of